Propensity score matching analysis of the relationship between allogeneic blood transfusion and postoperative pulmonary complications in scoliosis correction surgery: a retrospective study - Gao, Qi; Wang, Tingting; Zhou, Junyu; Wang, Ruiyu; Yu, Yang; Chen, Zexin; Chen, Yuexiu; Zou, Jingcheng; Zhao, Linqian; Yao, Yuanyuan; Zheng, Bin; Yan, Min (Frontiers in Medicine, 2025)
BackgroundSurgery is still the treatment of choice for patients with moderate to severe scoliosis, and vertebral column resection can significantly correct scoliosis. However, scoliosis correction surgery is associated with a high incidence of perioperative complications. We hypothesize that receiving allogeneic blood transfusions during surgery increases the risk of these complications in patients undergoing scoliosis correction surgery.MethodsThis retrospective study included 512 patients who underwent scoliosis correction surgery at the Second Hospital of Zhejiang University School of Medicine between August 2016 and April 2023. Patients who experienced or did not experience transfusion were balanced in terms of baseline clinicodemographic characteristics using propensity score matching. Multivariable logistic regression of the balanced data was performed to assess the potential influence of intraoperative allogeneic transfusion on incidence of PPCs.ResultsPropensity score matching led to a dataset of 322 patients, of whom 161 experienced allogeneic transfusion and 161 did not. Multifactorial logistic regression identified the following factors associated with PPCs: intraoperative allogeneic red blood cell transfusion rate (Risk Ratio (RR) 1.53 95% confidence interval (CI) 1.12–2.11, p = 0.007). The risk of PPCs increased with increasing volume of allogeneic blood transfusions, with those receiving 400 mL and more being at greater risk compared to those receiving no more than 400 mL (RR 1.40, 95% CI 1.04–1.89, p = 0.030). Subgroup analyses showed increased PPC risk in females, longer surgeries (>3 h), and patients without TXA use.ConclusionIntraoperative allogeneic red blood cell transfusion rate and volume during scoliosis correction surgery may be strongly associated with occurrence of PPCs.